A covariance based method to describe power processing in power electronics converters - Eardley, Arlo (My University, 2022)
This paper explores the use of a new topology evaluation framework to describe the internal power processing of a power electronics converter. This method is called the matrix method and leverages off a covariance matrix to describe power processing patterns in a power electronics converter. Covariance measures how two signals interact with each other. The covarianc between the power waveforms of the components in a converter describes how these components interact in terms of power. These are called “power interactions”. These power interactions between component powers provide insight into the power processing of a topology. The covariance matrix contains all combinations of component power pairs. This aims to describe all the power interactions components have in the entire converter. The covariance matrix is interpreted as describing the power processing inside a converter, where circulating power is occurring and which components are most involved in power processing. The covariance matrices of converters are able to be compared in a quantitative manner with the aim of providing a more justifiable reason for topology selection rather than personal bias. The matrix method is shown to be aligned with the principles of differential power theories. The matrix method is shown to be useful in comparing topologies, aiding in the topology selection process
A research report submitted to the School of Electrical and Information, Faculty of Engineering and the Built Environment, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Science in Engineering, 2022
Keywords: Topology Selection; DC-DC Converter; Power Processing; Covariance; Power Interactions; SDG-7: Affordable and clean energy